Model Of Labor Dispute Resolution On Cases Of Union Busting In Indonesia And The Usa - Martinouva, Rissa Afni; Effendi, Nurlis Effendi (Jurnal Hukum Malahayati, 2024)
This research examines the dispute resolution model concerning cases of union busting in Indonesia and the United States. Dispute resolution is crucial in the context of global industrial relations, considering the differences in legal systems, cultures, and labor policies between the two countries. Through a comparative legal approach, this article analyzes the legal framework in Indonesia and the United States related to union busting. Dispute resolution models, including mediation, arbitration, and litigation, are explored to understand their effectiveness and challenges in each legal context. The study employs references from labor laws, government policies, and recent legal cases to provide deeper insights. The results of this research are expected to serve as a foundation for improving and harmonizing labor dispute resolution systems in Indonesia and the United States, aligning with global efforts to enhance worker protection.